2002
DOI: 10.1523/jneurosci.22-12-04833.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function of Monomeric Amyloid β-Protein Serving as an Antioxidant Molecule against Metal-Induced Oxidative Damage

Abstract: Aggregated and oligomeric amyloid beta-protein (Abeta) is known to exhibit neurotoxicity. However, the action of Abeta monomers on neurons is not fully understood. We have studied aggregation state-dependent actions of Abeta and found an oligomer-specific effect of Abeta on lipid metabolism in neurons (Michikawa et al., 2001). Here, we show a novel function of monomeric Abeta1-40, which is the major species found in physiological fluid, as a natural antioxidant molecule that prevents neuronal death caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
246
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(263 citation statements)
references
References 53 publications
16
246
0
1
Order By: Relevance
“…32,33 Recent studies suggested that monomeric (soluble) Ab acts as a natural antioxidant that prevents neuronal cell death caused by oxidative stress, whereas fibrillar Ab is an ROS generator and neurotoxic. 34 Gly33 and Met35 of Ab 1-42 peptide have been reported to be essential for ROS production and neurotoxicity. 35 However, the precise molecular mechanism by which Ab leads to neuronal cell death has not been elucidated.…”
Section: Ask1 Is Required For Ab-induced Jnk Activation and Neuronal mentioning
confidence: 99%
See 2 more Smart Citations
“…32,33 Recent studies suggested that monomeric (soluble) Ab acts as a natural antioxidant that prevents neuronal cell death caused by oxidative stress, whereas fibrillar Ab is an ROS generator and neurotoxic. 34 Gly33 and Met35 of Ab 1-42 peptide have been reported to be essential for ROS production and neurotoxicity. 35 However, the precise molecular mechanism by which Ab leads to neuronal cell death has not been elucidated.…”
Section: Ask1 Is Required For Ab-induced Jnk Activation and Neuronal mentioning
confidence: 99%
“…Ab [25][26][27][28][29][30][31][32][33][34][35] and Ab 1-42 were purchased from Bachem and American Peptide Company, respectively. Ab [25][26][27][28][29][30][31][32][33][34][35] was dissolved in water at 1 mM and Ab was dissolved in water containing 0.1% NH 3 at 1 mM.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologic functions of A β are not well‐established, but significant lines of evidence suggest that A β may have potential protective properties under certain conditions. A β 42 has been shown to have antioxidant effects and decrease the oxidation of lipoproteins in the cerebrospinal fluid (CSF) and blood plasma 11, 12. A study utilizing different experimental autoimmune encephalomyelitis models, demonstrated that the peripherally augmented levels of A β 40 and A β 42 effectively suppressed inflammation in different organs, thus attenuating autoimmune inflammation targeting the central nervous system (CNS) 13.…”
Section: Introductionmentioning
confidence: 99%
“…The density of plaques containing Aβ protein correlates inversely with markers of oxidative damage (42), and in Downs syndrome, cortical deposition of Aβ proteins correlates with reduced oxidative damage (43). Moreover, Aβ proteins prevent lipoprotein oxidation (37) and metal-induced neuronal death in culture (44).…”
mentioning
confidence: 99%